2017
DOI: 10.1371/journal.pone.0185908
|View full text |Cite
|
Sign up to set email alerts
|

Ideal cardiovascular health predicts lower risk of abnormal liver enzymes levels in the Chilean National Health Survey (2009–2010)

Abstract: High levels of gamma glutamyltransferase (gamma-GT) and alanine aminotransferase (ALT), as well as fatty liver index (FLI) has been associated with higher cardiovascular disease risk factors in adults. The aim of this study was to examine the relationship between gamma-GT, ALT, and fatty liver index FLI levels across a gradient number of ideal cardiovascular health metrics in a representative sample of adults from the Chilean National Health Survey 2009–2010. Data from 1,023 men and 1,449 women (≥ 15 years) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
1
2
0
1
Order By: Relevance
“…What is the mechanism beyond elevation of liver enzymes among patients with MS. It seems that accumulation of fat in hepatocyte is associated [17,18] with picture of NAFLD particularly with hypertriglyceridemia, diabetes and obesity results in hepatocyte oxidative stress and injury and a sort of inflammation within the liver tissue [19] and in our study these conclusions were reinforced by higher prevalence of MS (42.4%) among subjects with elevated ALT (the most specific liver enzyme) when compared with AST and ALP. This have been also reported in some studies [14,[20][21][22].…”
Section: Discussionsupporting
confidence: 54%
“…What is the mechanism beyond elevation of liver enzymes among patients with MS. It seems that accumulation of fat in hepatocyte is associated [17,18] with picture of NAFLD particularly with hypertriglyceridemia, diabetes and obesity results in hepatocyte oxidative stress and injury and a sort of inflammation within the liver tissue [19] and in our study these conclusions were reinforced by higher prevalence of MS (42.4%) among subjects with elevated ALT (the most specific liver enzyme) when compared with AST and ALP. This have been also reported in some studies [14,[20][21][22].…”
Section: Discussionsupporting
confidence: 54%
“…Many epidemiological studies have used ALT and AST levels as measures to assess fat accumulation in hepatocytes. Increased ALT levels were associated with a higher likelihood of obesity, hypertension, hypertriglyceridemia, elevated blood glucose, and cardiovascular disease [ 15 , 25 , 26 ]. Furthermore, recent studies have reported the association of serum ALT and AST levels with MS [ 27 ] and its components [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the participants were categorized into 1 of 3 health levels based on the number of CVH metrics in the ideal range that they exhibited: the healthiest level (favorable ideal CVH score) was defined as having between 5 and 7 metrics in the ideal range; the intermediate level, 3 to 4 metrics; and the unfavorable level, 0 to 2 metrics. These cut-off points have been used in prior international studies [33].…”
Section: Methodsmentioning
confidence: 99%